Saving the World by Your Self: Comparing the Effects of Self-Assessment and Self-Improvement Message Strategies on Pro-Environmental Information Selection and Persuasive Outcomes. Issue 7 (3rd October 2021) - Luong, Kate T.; Knobloch-Westerwick, Silvia; Brooks, Dana
ABSTRACT: The effectiveness of behavioral change message strategies invoking the self-assessment (i.e. focusing on evaluating current behaviors) and the self-improvement (i.e. focusing on improving future behaviors) motives on pro-environmental information selection and subsequent pro-environmental beliefs, attitudes, and behavioral intentions were examined. The Selective Exposure and Self- and Affect Management (SESAM) model and the self-affirmation theory offered predictions for audiences with varying levels of environmental domain importance and perceived self-discrepancy. An online experiment was conducted, and the results showed that consistent with expectations, self-assessment message strategy was more effective for audiences with low perceived self-discrepancy, and self-improvement message strategy was more effective for audiences high on this individual characteristic. This interaction was most pronounced for audiences with high domain importance. Implications of the findings on theory and practice were discussed.